Caracterização anatômica da folha de Cymbopogon citratus (DC.) Stapf (Poaceae) e perfil químico do óleo essencial - Martins, M. B G [UNESP]; Martins, A. R. [UNESP]; Telascrêa, M. [UNESP]; Cavalheiro, Alberto José [UNESP] (My University, 2004)
The objective of the work was to accomplish an anatomical and ultrastructural study of mature leaf of Cymbopogon citratus (Poaceae) and analyze the essential oil through Gas Chromatography (GC). For the anatomical study, the material was fixed in FAA, followed bytheethyl dehydration and infiltration of the material in synthetic resin. For the ultrastructural study, the material was fixed and Kamovsky, dehydrated in acetone, dried to the critical point and metallized. For the analysis in GC, the essential oil it was obtained by steam distillation of leaves and analyzed by Gas Chromatography. Through the anatomical study it was observed that the faces of mesophyll are distinctly, the bulliform cells occupy the adaxial surface of the leaf and in the medium region are situated the biggest vascular bundles involved by sclerenchymatous hem with extensions reaching both epidermis. Between the biggest vascular bundles are observed three to five small vascular bundles, linkage only in the abaxial epidermis. Shortly, pointed and unicellular structures, called prickle-hair, had been observed inserted above the veins and micro-hair, that they consist of a long basal cell and an oval distal cell, that are located between the regions of vascular bundles. The chromatogram sample shows that the analyzed essential oil presented three majority components, responsible for 87% of the relative composition of the oil. These components are monoterpenos, justifying the strong smell of the essential oil.
Anatomical characterization of leaf of Cymbopogon citratus (DC.) Stapf (Poaceae) and chemical profile of the essential oil
Keywords: Cymbopogon citratus; Essential oils; Leaf anatomy; Plants Medicinal; cymbopogon citratus extract; essential oil; plant extract; unclassified drug; basal cell; blood vessel; distillation; gas chromatography; medicinal plant; plant leaf; Poaceae; Cymbopogon